Evaluation of anatomical pelvic parameters between normal, healthy men and women using three-dimensional computed tomography: a cross-sectional study of sex-specific and age-specific differences - Norio Imai; Hayato Suzuki; Asami Nozaki; Dai Miyasaka; Kazuki Tsuchiya; Tomoyuki Ito; Izumi Minato; Naoto Endo (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Background Sagittal spinal balance and standing posture are affected by pelvic morphology, especially pelvic incidence (PI). However, it is not difficult to identify the hip center because of overlap of the pelvis, image contrast, and soft tissue artifacts. Measurements of PI are not always suitable in all patients, especially those with osteoarthritis of the hip joint whose femoral head is nonspherical, subluxed, or dislocated. We measured PI, pelvic tilt (PT), and sacral slope (SS) as anatomical parameters using a novel three-dimensional measurement in order to compare the pelvic morphology between normal, healthy men and women. Methods In this cross-sectional study, we evaluated 108 Japanese subjects (55 men, 53 women) without low back or knee pain. We used the three-dimensional pelvis model adjusted to the anterior pelvic plane and measured the pelvic parameters. The subjects were stratified by age (< 50 versus ≥ 50 years) and sex. Intraobserver and interobserver reliabilities were calculated with intraclass correlation coefficients. Results There was no significant difference in PI, anatomical-PT, and anatomical-SS between sexes. There was a strong correlation between PI and anatomical-SS in men and women (R = 0.790 and 0.715, respectively). Values of anatomical-PT were lower, and values of anatomical-SS were greater among older subjects than among younger subjects; the value of PI was similar between younger and older subjects. Intraobserver and interobserver mean absolute differences were about 2 mm and 2°, respectively; the intraclass correlation coefficient was > 0.87. Conclusions We found a strong correlation between PI and anatomical-SS in men and women. This novel measurement concept may be useful to estimate PI from anatomical-SS because the measurements of PI are not always suitable in all patients, especially those with osteoarthritis of the hip joint whose femoral head is not spherical or whose femoral head is subluxed or dislocated. This is the first report to describe the relationship between PI, anatomical-PT, and anatomical-SS as morphologic parameters with a high interclass correlation coefficient for intraobserver and interobserver reliabilities.